Site‐Selective Tertiary Alkyl–Fluorine Bond Formation from α‐Bromoamides Using a Copper/CsF Catalyst System. Issue 34 (10th June 2016) - Nishikata, Takashi; Ishida, Syo; Fujimoto, Ryo
Abstract: A copper‐catalyzed site‐selective fluorination of α‐bromoamides possessing multiple reaction sites, such as primary and secondary alkyl−Br bonds, using inexpensive CsF is reported. Tertiary alkyl−F bonds, which are very difficult to synthesize, can be formed by this fluorination reaction with the aid of an amide group. Control experiments revealed that in situ generated CuF2 is a key fluorinating reagent that reacts with the tertiary alkyl radicals generated by the reaction between an α‐bromocarbonyl compound and a copper(I) salt. Abstract : A picky copper : A copper catalyst system enables the site‐selective fluorination of multi‐brominated tertiary‐alkyl compounds with the aid of an amide group. As the fluorination reagent, inexpensive CsF is used, and CuF2 was found to be a reactive intermediate.